REGULATIONS IN THE LEGAL SYSTEM OF THE REPUBLIC OF SERBIA - Stevandić, Danilo (Pravni zapisi, 2013)
In the legal system established by the Republic of Serbia Constitution of 2006, regulations are legal acts adopted by the Government pursuant to its constitutional or statutory powers, in the procedure it regulates itself, with the purpose of executing statutes. The legal system does not recognise the domain of primary power to adopt regulations nor the institute of delegated legislation (in the narrow sense) and, consequently, the Government cannot regulate issues that are in the competence of the legislative power by its regulations. In order to perform the powers vested with it by the constitution and by statutes, the Government may adopt executive, and, exceptionally, emergency regulations. In the legal regulations’ system the regulations are positioned below the Constitution, generally accepted rules of international law, ratified international agreements and statutes, but above other secondary general acts. Their position is conditioned by the position that the Government, which adopts them, has in the parliamentary system of organisation of powers. The Constitutional Court controls regulations a posteriori in an abstract dispute concerning constitutionality and legality. Ever since the 2006 Constitution is valid, the regulatory activity of the Government was somewhat more intense compared to the legislative activity of the National Assembly. When effecting its regulatory power, in a number of cases the Government had exceeded its constitutional and legislative powers concerning the subject-matter being regulated, thus violating the principle of separation of powers from Article 4 paragraph 2 of the Constitution.
Keywords: regulation; Constitution of the Republic of Serbia; the principle of separation of powers; the National Assembly; general regulations; executive regulations; emergency regulations; the Constitutional Court; assessment of constitutionality and legality.